1996
DOI: 10.1084/jem.183.6.2559
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 primes human CD4 and CD8 T cell clones for high production of both interferon-gamma and interleukin-10.

Abstract: SUmlTlaryInterleukin-12 (IL-12) induces differentiation of T helper 1 (Thl) cells, primarily through its ability to prime T cells for high interferon-~/ (IFN-~) production. We now report that the presence of IL-12 during the first several days of in vitro clonal expansion in bruiting dilution cultures of polyclonally stimulated human peripheral blood CD4 + and CD8 + T cells also induces stable priming for high IL-10 production. This effect was demonstrated with T cells from both healthy donors and HIV(+) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
160
1
4

Year Published

1997
1997
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(183 citation statements)
references
References 61 publications
18
160
1
4
Order By: Relevance
“…Conversely, the addition of IFN-g, anti-IL-4 or IL-12 to in-vitro cultures of in-vivo primed T cells shifted the cytokine pattern of memory T cells to a Th1-like profile in murine [15,18] as well as in human T cell immune responses [17,19]. These results correspond to the results of two studies published while this manuscript was in preparation [21,22]. Meyaard and coworkers showed that IL-12 induced IL-10 production in freshly isolated human T cells as well as in T cell clones.…”
Section: Frequency and Cytokine Profiles Of Tumour Reactive Cd4 + T Csupporting
confidence: 78%
See 1 more Smart Citation
“…Conversely, the addition of IFN-g, anti-IL-4 or IL-12 to in-vitro cultures of in-vivo primed T cells shifted the cytokine pattern of memory T cells to a Th1-like profile in murine [15,18] as well as in human T cell immune responses [17,19]. These results correspond to the results of two studies published while this manuscript was in preparation [21,22]. Meyaard and coworkers showed that IL-12 induced IL-10 production in freshly isolated human T cells as well as in T cell clones.…”
Section: Frequency and Cytokine Profiles Of Tumour Reactive Cd4 + T Csupporting
confidence: 78%
“…Gerosa and coworkers showed that polyclonally stimulated CD4 + and CD8 + T cell clones, which were established in the presence of IL-12, produced high levels of IL-10 and IFN-g. In contrast, IL-4 suppressed the development of IL-10 producing T cell clones [22]. Corresponding to these in vitro results, IL-12 injection into mice induced the production of IL-10 and IFN-g in vivo [23].…”
Section: Frequency and Cytokine Profiles Of Tumour Reactive Cd4 + T Cmentioning
confidence: 99%
“…We also examined the expression of IL-10, which is known to be induced in both neonates and adult mice by IL-12 treatment (23,28,29). Analysis of neonatal splenic mRNA revealed an absence of IL-10 mRNA expression in animals that received vaccine alone or PBS-NMS alone.…”
Section: H1n1 Subunit Vaccine Plus Il-12 Administration To Neonates Ementioning
confidence: 99%
“…RIAs for human IL-12 p40, IL-12 p70, TNF-␣, and IL-10 were performed as previously described (21)(22)(23)(24), using mAb pairs C11.79/C8.6, 12H4/C8.6, B154.9/B154.7, and 9D7/12G8, respectively.…”
Section: Human Pbmc Infection and Cytokine Measurementmentioning
confidence: 99%